PERANCANGAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI PADA LEMBAGA MA DINIYAH PUTRI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH MENGGUNAKAN METODE TOGAF ADM - Akhlis Munazilin; Sidra Al Sehro; Nur Laili Mukarromah (Jurnal Riset Teknik Komputer, 2026)
The development of information technology encourages educational institutions to have an integrated information system to support academic and administrative processes. MA Diniyah Putri, Pondok Pesantren Salafiyah Syafi'iyah still faces the problem of unintegrated data management. This study aims to design an information system enterprise architecture using The Open Group Architecture Framework (TOGAF) through the Architecture Development Method (ADM). Data collection was carried out through observation, interviews, and document analysis. The results of the study produced an enterprise architecture blueprint that includes business, data, application, and technology architecture, as well as a gradual implementation roadmap as a guide for information system development. The application of TOGAF ADM is considered effective in producing a structured and long-term oriented information system design, and has the potential to improve information governance and support digital transformation in the MA Diniyah Putri environment of Pondok Pesantren Salafiyah Syafi'iyah.